2019
DOI: 10.13102/sociobiology.v66i3.3463
|View full text |Cite
|
Sign up to set email alerts
|

Bees (Hymenoptera, Apoidea) in an Ecotonal Cerrado-Amazon Region in Brazil

Abstract: Little is known about the composition of the bee community in the Cerrado-Amazon transition area. Herein, we present the results of a bee survey done within the municipality of Conceição do Araguaia, in the state of Pará. Six fragments were sampled twice (once in the dry season and once in the rainy season) using three methods of collecting: arboreal pitfalls with urine, scent traps, and pan traps. We recorded 67 bee species, distributed in 28 genera and eight tribes. Except for Partamona chapadicola, which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 28 publications
4
9
0
4
Order By: Relevance
“…Furthermore, bee species' richness can be even higher in ecotone regions between Cerrado areas and the Amazon Rainforest, and important concerning the limits distribution in any of the biomes taken into account in the transition site. A good example of it is the study carried out in this transition area type, which reported that the bees' community held 15 species endemics to the Amazonian region, one species endemic to Cerrado, and 27 species common to both the Amazon Rainforest and Cerrado (Almeida et al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, bee species' richness can be even higher in ecotone regions between Cerrado areas and the Amazon Rainforest, and important concerning the limits distribution in any of the biomes taken into account in the transition site. A good example of it is the study carried out in this transition area type, which reported that the bees' community held 15 species endemics to the Amazonian region, one species endemic to Cerrado, and 27 species common to both the Amazon Rainforest and Cerrado (Almeida et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the publish studies only take into account the diversity of specific tribes, such as Meliponini or Euglossini (Roel et al 2019, Oliveira-Junior et al 2015. Besides, most surveys only use one collection method (Santiago et al 2009, Roel et al 2019, Santos et al 2004, and only few of them use more than one collection method (Almeida et al 2019, Ferreira et al 2019.…”
Section: Introductionmentioning
confidence: 99%
“…A maioria dos estudos (n=39; 88,63%) utilizou apenas um método de coleta, sendo "Busca Ativa" (n=25) o mais utilizado, seguido de "Busca por Ninhos" (n=13) e somente um estudo (Silva, 2019) que utilizou "Möericke" como método principal. Entretanto, o ideal seria que os trabalhos conciliassem e sistematizassem vários métodos a fim de obter melhor eficiência na amostragem, registrando assim, maior número de espécies de Meliponina em determinada área [29,30,31], assim como já foi registrado um acréscimo de espécies, devido ao consórcio de métodos, para outros Hymenoptera, como as vespas sociais [32]. Contudo, vale destacar que a elaboração e utilização de métodos devem ser baseadas na biologia e ecologia dos animais estudados a fim de evitar um esforço ineficaz durante a realização do estudo.…”
Section: Resultsunclassified
“…Thus, we find ourselves in a situation of aggravating loss of the diversity of bees, and we do not even know many of the species in the national territory. Although research on the diversity of Brazilian bee fauna has occurred frequently in recent years (Viana & Lourenço, 2020;Almeida et al, 2019), the vastness of the Brazilian territory prevents all areas from being covered with this type of work, thus leaving some regions lacking such information, mainly restricted access regions, such as islands off the Brazilian coast, for example.…”
Section: Introductionmentioning
confidence: 99%